Views of Academic Staff in Universities on Lifelong Learning and Adult Education - Karakoc, Berna (Asian Journal of Education and Training, 2021)
The general aim of this study is to find out the views of academic staff working at universities on lifelong learning and adult education. While finding out the views of academic staff, the 6 principles of Andragogy Approach, which includes the characteristics of adults about learning, were taken as basis and the professional or personal development trainings academic staff received were analysed separately within the framework of these principles. Interview technique, one of the most frequently used in qualitative research methods, was used in the study. Interviews were made with a total of 20 academic staff who had received training within the scope of adult education and lifelong learning. The interviews were recorded with a voice recorder and transcribed. The transcribed data were evaluated with descriptive analysis method and then they were coded. Interpretations were made by using the codes. As a result, it was found that the academic staff in general had received education on lifelong learning and adult education voluntarily and it was concluded that they received these trainings for professional or personal development, to increase their quality of life, to gain experience, to advance academically and for similar reasons.